PENGARUH LOCUS OF CONTROL TERHADAP HUBUNGAN SIKAP MANAJER, NORMA-NORMA SUBYEKTIF, KENDALI PERILAKU PERSEPSIAN, DAN INTENSI MANAJER DALAM MELAKUKAN KECURANGAN PENYAJIAN LAPORAN KEUANGAN - Wening, Novita (Jurnal Akuntansi dan Keuangan Indonesia, 2011)
This research adopts the theory of planned behavior. The purpose of this research is to examine the effects of attitude toward behavior, subjective norms, and perceived behavioral control on the manager’s intention to commit fraudulent financial reporting moderated by locus of control. This research applies a mail survey as data collection method and judgment sampling as sample collection method. Research subjects are accounting and finance managers of manufacture industry in Indonesia. There are 1,700 questioners to be distributed during the research. However, there are only 148 of the 186 returned questioners to be included in the research analysis. Empirical evidence finds that locus of control moderates the effect of attitude toward behavior and subjective norms on the manager’s intentions to commit fraudulent financial reporting. However, locus of control does not moderate the effect of perceived behavioral control on the manager’s intentions to commit fraudulent financial reporting. These results indicate that the presence of locus of control - which is the belief in one's self - strengthen the influence of attitudes and subjective norms to make a fraudulent financial statements into action.